PENGARUH CORPORATE GOVERNANCE DAN LEVERAGE TERHADAP TAX AVOIDANCE PADA PERUSAHAAN MANUFAKTUR YANG TERDAFTAR DI BURSA EFEK INDONESIA (BEI) TAHUN 2011-2015 - Marfirah, Dina; BZ, Fazli Syam (Jurnal Ilmiah Mahasiswa Ekonomi Akuntansi, 2016)
The purpose of this study was to examine the influence of institutional ownership, board of directors, audit quality, audit committee, and leverage against tax avoidance. The population in this research is manufacturing companies listed in Indonesia Stock Exchange during 2011 to 2015 with the number of 132 companies. The samples were selected in the study using purposive sampling method. Testing the influence of institutional ownership, board of directors, audit quality, audit committee, and leverage against tax avoidance measures. Research analysis using multiple linear regression with SPSS 20.0. The results showed there were 46 companies meeting the targets set out in the study population. Based on the test results of multiple linear analysis with a significance level of 35.8%, the results of this study concluded that: (1) institutional ownership effect on tax avoidance (2) commissioners effect on tax avoidance (3) The tax effect on audit quality avoidance (4) audit committee influence on tax avoidance (5) the leverage effect on tax avoidance.Keywords : institutional ownership , board of directors , audit quality , audit committee , leverage , tax avoidance .